2021 Elijah High-Altitude Balloon Payload - Kalish, Julia; Gutierrez, Jorge; Salazar, Bryanna; Cioni, Jordan (Proceedings of the Wisconsin Space Conference, 2022)
The 2021 WSGC Elijah High-Altitude Balloon Payload Team focused their projects on the upcoming 2024 solar eclipse. These included solar sensing, solar imaging, and the study of cosmic radiation. The solar sensing project involved collecting flight data such as altitude, temperature, and pressure. In addition to this data, quantitative UVA, UVB, light intensity, and solar energy values using various sensors and solar panels. Solar imaging utilized an action camera with solar, IR, and IR cut-off filters in conjunction with a 360-degree camera that captured the entire payload’s flight. The radiation shielding project focused on studying the effectiveness of low-density polyethylene as a radiation shielding material by comparing observations collected by shielded and unshielded Geiger counters. To observe radiation originating from nearby star systems, a particle detector consisting of a scintillator coupled to a silicon photomultiplier was constructed.